Animal models to achieve an HIV cure. Issue 4 (July 2016) - Kumar, Nitasha; Chahroudi, Ann; Silvestri, Guido
Abstract : Purpose of review: The introduction of effective antiretroviral therapy (ART) has transformed HIV infection from a deadly to a chronic infection. Despite its successes in reducing mortality, ART fails to cure HIV allowing HIV to persist in vivo . HIV persistence under ART is thought to be mediated by a combination of latent infection of long-lived cells, homeostatic proliferation of latently infected cells, anatomic sanctuaries, and low-level virus replication. To understand the contribution of specific cell types and anatomic sites to virus persistence in vivo animal models are necessary. Recent findings: The advancements in ART and our understanding of animal models have facilitated the development of models of HIV persistence in nonhuman primates and mice. Simian immunodeficiency virus (SIV) or simian/HIV infection (SHIV) of rhesus and pigtail macaques followed by effective ART represents the most faithful animal model of HIV persistence. HIV infection of humanized mice also provides a useful model for answering specific questions regarding virus persistence in a uniquely mutable system. Summary: In this review, we describe the most recent findings using animal models of HIV persistence. We will first describe the important aspects of HIV infection that SIV/SHIV infection of nonhuman primates are able to recapitulate, then we will discuss some recent studies that have used these models to understand viral persistence.